2009
DOI: 10.3109/08941930903410783
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neopterin as a Prognostic Indicator in Patients with Gastric Carcinoma

Abstract: Serum neopterin levels were elevated in patients with advanced gastric cancer and correlated with prognostic parameters and overall survival. Moreover, neopterin measured at the time of diagnosis can be used to predict the survival of gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 31 publications
0
21
2
Order By: Relevance
“…We assessed the diagnostic utility of neopterin, which elevated serum and urinary levels were reported in breast, gastric and colon cancer [5,6,8]. We – as well as Birk et al [10] – observed elevated neopterin serum levels in patients with PA compared to the CP and healthy groups.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We assessed the diagnostic utility of neopterin, which elevated serum and urinary levels were reported in breast, gastric and colon cancer [5,6,8]. We – as well as Birk et al [10] – observed elevated neopterin serum levels in patients with PA compared to the CP and healthy groups.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, Yildrim et al [5] found that the serum levels of neopterin were higher in patients with metastatic breast cancer compared to patients without distal metastases. Unal et al [8] also observed that serum neopterin concentrations were significantly higher in patients with gastric carcinoma than in the control group and were correlated with tumor stage, gastric wall involvement and the number of metastatic lymph nodes. In study of Birk et al [10], higher neopterin serum levels were also an independent prognostic factor in resectable PA patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Hysteroscopy, although not required, is recommended with directed dilatation and curettage to include any discrete lesions and background endometrium. 2 In several studies, the urine and serum levels of neopterin were found to be high in the advanced stages of the disease as well as in the cases of metastases and recurrence, particularly in prostate cancer, 3 lung cancer, 4 cancers linked to the gastrointestinal system, 5,6 and in other types of cancer such as breast 7 and thyroid. 8 While it has been observed that the urine neopterin levels of women with gynecological precancerous lesions and women with benign tumors are not different from that of the neopterin levels in healthy women.…”
mentioning
confidence: 99%
“…It is increased in diseases where the cellular immune system is activated; autoimmune diseases [multiple sclerosis (MS), rheumatoid arthritis (RA)], infections (HIV), and also in some cancer types (ovarian carcinoma, uterine tumors, colon cancer, breast cancer, leukemia and lymphoma) [6][7][8][9][10][11][12]. It is used as a prognostic marker [13][14][15][16] and can show the stage of the disease [17]. Additionally it can increase in metastatic rather than local diseases [18].…”
Section: Introductionmentioning
confidence: 99%